Percepção ambiental do manejo dos resíduos sólidos: o caso de Lucrécia/RN - Alves, Adriana Maria (Universidade Federal Rural do Semi-Árido, 2019)
Incorrect waste disposal is responsible for numerous environmental problems, generating a number of inconveniences for the population. Solving these problems is not an easy task, but something needs to be done to at least minimize the damage done. The present work aimed to investigate the knowledge of the population of Lucrécia Rio Grande do Norte, about the waste disposal in the city. From the field research, it was possible to realize that 82% of people do not care about storing the waste properly, besides not giving importance to the waste they produce, 76% do not worry about separating organic waste from solid waste and 57% reuse some materials. Of those interviewed 43% do not care about the destination of garbage, has no critical sense to question with the rulers for public policies aimed at valuing the environment. In conclusion, it is necessary, first of all, to invest in environmental education and in raising public awareness about the importance of adopting an appropriate social and environmental responsibility in relation to the management of solid waste produced.
Keywords: Geração de lixo; Responsabilidade socioambiental; Pequenas cidades; Waste generation; Social and environmental responsibility; Environmental education; Semi-arid; Small cities; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA